2018
DOI: 10.1021/jacs.8b05518
|View full text |Cite
|
Sign up to set email alerts
|

Highly Ambiphilic Room Temperature Stable Six-Membered Cyclic (Alkyl)(amino)carbenes

Abstract: Cyclic (alkyl)(amino)carbenes with a six-membered backbone were prepared. Compared to their five-membered analogues, they feature increased % V and enhanced donor and acceptor properties, as evidenced by the observed n → π* transition trailing into the visible region. The high ambiphilic character even allows for the intramolecular insertion of the carbene into an unactivated C(sp)-H bond. When used as ligands, they outcompete the five-membered analogues in the palladium-mediated α-arylation of ketones with ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
122
2
13

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 124 publications
(144 citation statements)
references
References 83 publications
7
122
2
13
Order By: Relevance
“…Further, analysis of the steric maps indicated that the additional steric hindrance in 5 is also placed around the north to south axis, which probably prevents coordination of bulky substrates, while in the steric map of 6 these are relatively unhindered zones, which possibly allows for coordination of bulkier substrates. Subsequent comparison of the catalytic activities of 4, 5, and 6 in the α-arylation of propiophenone with different aryl chlorides indicated that CAAC-6 complex 6 outperforms CAAC-5 complexes 4 and 5, and it offers excellent yields regardless of the structure of the aryl chloride (Figure 4a), validating the catalyst design strategy 40 .…”
Section: Topographic Steric Maps In Catalyst Designmentioning
confidence: 69%
See 1 more Smart Citation
“…Further, analysis of the steric maps indicated that the additional steric hindrance in 5 is also placed around the north to south axis, which probably prevents coordination of bulky substrates, while in the steric map of 6 these are relatively unhindered zones, which possibly allows for coordination of bulkier substrates. Subsequent comparison of the catalytic activities of 4, 5, and 6 in the α-arylation of propiophenone with different aryl chlorides indicated that CAAC-6 complex 6 outperforms CAAC-5 complexes 4 and 5, and it offers excellent yields regardless of the structure of the aryl chloride (Figure 4a), validating the catalyst design strategy 40 .…”
Section: Topographic Steric Maps In Catalyst Designmentioning
confidence: 69%
“…Topographic steric maps can be a useful guide for the design of new catalysts because they enable the determination of the effect of structural changes. For example, Bertrand et al used topographic steric maps to design cyclic, six-membered (alkyl)(amino)carbene (CAAC-6) ligands capable of outcompeting their fivemembered analogues (CAAC-5) in Pd-mediated arylations of ketones with aryl chlorides (Figure 4a) 40 . Previous work on CAAC-5 Pd-complexes indicated that 4, with unhindered ethyl substituents, was unable to promote the -arylation reaction, while 5, with a bulky menthyl substituent replacing the ethyl groups, showed high reactivity with the less sterically demanding aryl chloride, i.e., chlorobenzene.…”
Section: Topographic Steric Maps In Catalyst Designmentioning
confidence: 99%
“…Obwohl 4 ein formales Fe 0 -Zentrum aufweist, wurde keine Oxidation des Metallzentrums beobachtet und der resultierende Komplex 6 weist, fürd iamagnetische Verbindungen übliche,g utaufgelçste NMR-Signale auf.D ie chemischen Verschiebungen von Selenoharnstoffen in 77 Se-NMR-Experimenten dienen als etablierte Methode um die p-Aciditätv on NHCs abzuschätzen. [1,14] Mit einem 77 Se-NMR-Signal bei 535 ppm liegt 2 tieffeldverschoben im Vergleich mit etablierten IPr (d Se = 87 ppm) und SIPr NHCs (d Se = 181 ppm), [1] zwischen Bertrands 5-gliedrigen cyclischen (Alkyl)(amino)carbenen (5-cAAC) (d Se = 492 ppm) und bicyclischen (Alkyl)(amino)carbenen BICAAC( d Se = 645 ppm), [15] in guter Übereinstimmung mit der experimentell beobachtbaren hohen Elektrophilie von 2. [16] Zur weiteren Untersuchung der elektronischen Struktur von 2 wurden die entsprechenden Rhodiumkomplexe synthetisiert.…”
Section: Ergebnisse Und Diskussionunclassified
“…Die Gesamtheit der spektroskopischen Daten stellen klar den ambiphilen Charakter des Carbens 2 heraus. [1,19] Die Ambiphilie kann durch die einzigartige Kombination eines Pyrazinringes mit einem Fe(CO) 2 Fragment erklärt werden. Während der Diazinring p-acide ist, kann das an das Eisenzentrum koordinierte Stickstoffatom nichts zur Stabilisierung des formal unbesetzten p p Orbitals des Carbens beitragen, da es an der koordinativen Bindung zum Eisenzentrum beteiligt ist (vide infra).…”
Section: Ergebnisse Und Diskussionunclassified
“…2-ethyl-N-(2-isopropyl-6-methylphenyl)butan-1-imine (S1). A procedure was adapted from the literature 2 as follows: A 20 mL vial was charged with 2-isopropyl-6-methylaniline (3.04 g, 20.4 mmol, 1.0 equiv), 2-ethylbutanal (2.04 g, 20.4 mmol, 1.0 equiv), magnesium sulfate (2.0 g, 16.6 mmol, 0.80 equiv), and CH2Cl2 (10 mL) in air. The vial was sealed and stirred vigorously at RT for 24 h. The reaction was filtered over celite and concentrated under reduced pressure.…”
mentioning
confidence: 99%